PENYULUHAN KESEHATAN MATA SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT DI BANJAR JAGATAMU, DESA MELILING, TABANAN - Ni Made Widya Mahayani; Ni Made Putri Suastari; AA Sagung Candra Mahesuari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Eye health education is an important to raise public awareness about the importance of maintaining eye health and preventing permanent eye damage. The Eye Health Education Program aims to provide information to maintain eye health, recognize symptoms of vision problems, and understand the importance of regular eye exams. This event was held at Banjar Jagatamu, Meliling, Kerambitan, Tabanan, Bali on November 17, 2024, with participation from the local community. During the session, participants were provided with information about common eye conditions, such as cataracts, pterygium, and dry eye disease, along with preventive measures. At the end of the event, a discussion session was held, and the participants were very enthusiastic. The outcome of this counseling session can increase public awareness about the importance of eye health and the prevention of avoidable blindness